Kondisi sosial ekonomi keluarga nelayan terhadap pendidikan anak di Desa Tolondadu Kecamatan Bolaang Uki Kabupaten Bolaang Mongondow Selatan - Mamuki, Emiliyan; Mohamad, Abdurahman K.; Damhuri, Agung (Universitas Halu Oleo, 2025)
This study aims to determine how the socio-economic conditions of fishermen's families affect the motivation and ability of children to continue formal education and to determine what impact the socio-economic conditions of fishermen's families have on the success and eligibility of their children's education in Tolondadu Village. The data analysis used is a quantitative descriptive approach, with data collection using a questionnaire, with a Likert scale to measure attitudes, opinions, and perceptions. Based on the results of the study, it shows that the socio-economic conditions of fishermen's families have a positive and significant influence on children's education in Tolondadu Village. In the context of education, support from good socio-economic conditions allows parents to meet their children's educational needs, such as buying books, stationery, school uniforms, and paying for quality education. And shows that good socio-economic conditions in fishermen's families in Tolondadu Village contribute positively to children's education. Families with better economic conditions, such as books, stationery and access to quality educational institutions